2020
DOI: 10.2147/dddt.s239458
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolic Stability Assessment of New PARP Inhibitor Talazoparib Using Validated LC–MS/MS Methodology: In silico Metabolic Vulnerability and Toxicity Studies</p>

Abstract: Background: Talazoparib (BMN673) is a new poly(ADP-ribose) polymerase inhibitor that has been FDA approved for patients suffering from metastatic breast cancer with germline BRCA mutations. Method and Results: In the current study, an accurate and efficient liquid chromatographytandem mass spectrometry (LC-MS/MS) analytical methodology was developed for TZB estimation in addition to its metabolic stability assessment. TZB and lapatinib (LAP) (which is chosen as an internal standard; IS) were separated using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…The CSL was 0.9983, which is considered high compared to other previously studied anti-cancer drugs (ex. Talazoparib) [30]. The outcomes from the WhichP450™ module of StarDrop software revealed that CYP3A4 was found to have a basic role in TEP metabolism, which proposed the high possibility of drug-drug interaction with other drugs that induce or inhibit CYP3A4 enzyme.…”
Section: Results Of In Silico Tep Metabolites Predictionmentioning
confidence: 99%
“…The CSL was 0.9983, which is considered high compared to other previously studied anti-cancer drugs (ex. Talazoparib) [30]. The outcomes from the WhichP450™ module of StarDrop software revealed that CYP3A4 was found to have a basic role in TEP metabolism, which proposed the high possibility of drug-drug interaction with other drugs that induce or inhibit CYP3A4 enzyme.…”
Section: Results Of In Silico Tep Metabolites Predictionmentioning
confidence: 99%
“…Hence, the detection sensitivity decreases when using MS/MS for scanning of unknown metabolites, limiting its usage. However, in case of metabolic stability studies, triple quadrupole instruments provide an excellent alternative to more expensive TOF/Q‐TOF analyzers, enabling both a reliable quantitative analysis (for metabolic stability estimation) and metabolite structure identification [11–19,23,52–60].…”
Section: Separation Techniques Used In Metabolic Stability Estimationmentioning
confidence: 99%
“…In paid options, Stardrop software seems to be one of the most valuable options. Apart from predicting sites of metabolism, Stardrop can also predict P450 metabolism, and is a valuable in silico tool to develop ADME QSAR models and explore metabolism in many creative pathways, depending on the chosen package [54,58,64,93–96].…”
Section: Chemometric Techniques Used In Metabolic Stability Model Devmentioning
confidence: 99%
“…Thus, nucleophile trapping can be utilized to seize the generated reactive species forming stable adducts that could be characterized using liquid chromatography-tandem mass spectrometry (LC-MS/MS). [23][24][25][26] The IUPAC designation of ESB is 6-amino-5- Figure 1). ESB chemical structure contains a dichloro-fluorophenyl ring and cyclic tertiary amine rings (piperazine).…”
Section: Introductionmentioning
confidence: 99%